Yolk-eggshell structure Bi2S3atC / Fe3O4 nano-particles as well as preparation method and application thereof
By preparing Bi2S3@C/Fe3O4 nanoparticles with an egg yolk-shell structure, and combining photothermal and radiotherapy, the deep penetration and targeting problems in the treatment of glioblastoma were solved, achieving synergistic ablation and precise treatment of tumors.
Patent Information
- Application Number
- CN202511113054.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-08
- Publication Date
- 2025-11-11
AI Technical Summary
Existing treatments for glioblastoma have side effects from surgery, radiotherapy, and chemotherapy. Furthermore, photothermal therapy and radiotherapy have limitations in terms of deep tumor penetration and targeting, and there is a lack of effective drug delivery platforms.
We developed a yolk-shell structure of Bi2S3@C/Fe3O4 nanoparticles, which combine a phenolic resin carbon shell layer and a Bi2S3 core layer with superparamagnetic Fe3O4 nanoparticles to achieve high near-infrared absorption and magnetic targeting of the nanoparticles for PTT-RT combined therapy.
It achieves highly efficient targeted delivery and synergistic treatment at the tumor site, overcomes the penetration depth limitations of photothermal therapy, enhances the deep effects of radiotherapy, and provides precise tumor ablation results.
Smart Images

Figure CN120919074A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of nanomaterials technology, specifically to a yolk-shell structured Bi2S3@C / Fe3O4 nanoparticle, its preparation method, and its applications. Background Technology
[0002] Treatment options for glioblastoma include surgery, radiotherapy, and chemotherapy. However, each treatment method may present the following challenges: First, surgery may lead to neurological impairment, such as motor, speech, or cognitive dysfunction. Furthermore, surgery carries the risk of infection and may cause cerebral edema, requiring medication. Second, radiotherapy may cause abnormal fatigue, and the skin in the irradiated area may experience redness, dryness, or peeling. It may also cause changes in brain function, such as decreased memory, attention, and learning ability, as well as headaches. Third, chemotherapy drugs may cause nausea and vomiting, and some patients may experience hair loss. Some chemotherapy drugs may also damage the peripheral nervous system, leading to sensory abnormalities such as numbness and tingling in the hands and feet. As an aggressive tumor, glioblastoma (GBM) typically possesses intrinsic radiation resistance, and most recurrences occur within the original irradiated area. The hypoxic state of the tumor microenvironment further exacerbates this resistance because it reduces radiation-induced DNA damage. In summary, the treatment of glioblastoma sometimes requires a combination of surgery, radiotherapy, and chemotherapy. Treatment plans need to be individualized based on the patient's specific situation, which places higher demands on the medical team.
[0003] Photothermal therapy (PTT) based on nanomaterials destroys tumor cells through thermal ablation. Precise control of parameters such as light source intensity (e.g., 808nm near-infrared laser), irradiation time, photothermal material concentration, particle size, and surface modification allows for precise ablation of tumor tissue. However, the tissue penetration depth of lasers is typically less than 5mm, often failing to eradicate deep-seated cancer cells, limiting the application of PTT in advanced or invasive tumors. Radiotherapy (RT) also suffers from limitations in its maximum tolerated dose due to the sensitivity of surrounding healthy tissue; simply increasing the dose cannot completely eradicate the tumor. The combined PTT-RT therapy offers a synergistic solution to overcome these limitations. PTT not only induces cancer cell necrosis or apoptosis through high heat (typically >42°C) but also remodels the tumor microenvironment to enhance oxygenation, thereby reducing resistance to RT. Conversely, the deep tissue penetration of RT compensates for the superficial reach of PTT, achieving comprehensive coverage of both superficial and deep tumor lesions. Preclinical studies have consistently shown that PTT-RT has a synergistic effect superior to monotherapy, and combination therapy can achieve a higher tumor regression rate. However, there is currently no suitable guided drug delivery platform that allows drugs to accumulate at the target site under the guidance of an external magnetic field.
[0004] Therefore, there is an urgent need to develop a nanomaterial that can cross the damaged blood-brain barrier in mid-to-late stage GBM and has highly efficient targeting at the tumor site, so as to use it in PTT-RT combined therapy for GBM and provide an effective method for synergistic treatment of neuro-oncology. Summary of the Invention
[0005] To address the aforementioned problems, the present invention aims to provide a yolk-shell structured Bi2S3@C / Fe3O4 nanoparticle, its preparation method, and its applications.
[0006] To achieve the above objectives, the present invention employs the following technical solution:
[0007] A yolk-eggshell structured Bi2S3@C / Fe3O4 nanoparticle comprises a carbon shell layer and a core layer, which are connected by a hollow layer. The carbon shell layer is made of phenolic resin carbon, and superparamagnetic Fe3O4 nanoparticles are uniformly distributed within it. The core layer is made of Bi2S3 nanoparticles. The size of the yolk-eggshell structured Bi2S3@C / Fe3O4 nanoparticles is 75–110 nm, the diameter of the core layer is 40–60 nm, and the thickness of the carbon shell layer is 5–25 nm.
[0008] Preferably, the saturation magnetization of the superparamagnetic Fe3O4 nanoparticles is 0.8 to 1.2 emu / g.
[0009] Preferably, the yolk-shell structured Bi2S3@C / Fe3O4 nanoparticles are loaded with drugs, such as temozolomide.
[0010] This invention also includes a method for preparing Bi2S3@C / Fe3O4 nanoparticles with an egg yolk-eggshell structure, comprising the following steps:
[0011] ①Preparation of Bi2S3 nanoparticles: Bismuth ammonium citrate, polyvinylpyrrolidone and deionized water were added to a reaction vessel, heated and stirred to obtain solution A;
[0012] Thioacetamide was added to deionized water and stirred under heating until completely dissolved to obtain solution B;
[0013] Solution B was added to solution A, the mixture was stirred, centrifuged, filtered, and the filter cake was washed with deionized water and ethanol to obtain Bi2S3 nanoparticles.
[0014] ② Preparation of egg yolk-eggshell structured Bi2S3@phenolic resin nanoparticles: The Bi2S3 nanoparticles obtained in step ① and 3-aminophenol were added to deionized water, sonicated, ammonia water was added, stirred, formaldehyde aqueous solution was added, stirred and mixed, acetone was added to the solution, stirring was continued, centrifuged, filtered, the filter cake was washed with deionized water and ethanol, and dried to obtain egg yolk-eggshell structured Bi2S3@phenolic resin nanoparticles;
[0015] ③ The egg yolk-eggshell structure Bi2S3@phenolic resin nanoparticles obtained in step ② are added to the reaction vessel, FeSO4 aqueous solution is added under vacuum, stirred and mixed, restored to atmospheric pressure, filtered to remove excess liquid, the filter cake is dried, and sintered at high temperature under argon atmosphere to obtain egg yolk-eggshell structure Bi2S3@C / Fe3O4 nanoparticles.
[0016] Preferably, it includes the following steps:
[0017] ①Preparation of Bi2S3 nanoparticles: 0.3-1.3 parts by weight of bismuth ammonium citrate, 0.2-1 parts by weight of polyvinylpyrrolidone and 25-50 parts by weight of deionized water were added to a reaction vessel, heated to 25-95℃, and stirred to obtain solution A.
[0018] Add 0.75–3 parts of thioacetamide to 10–50 parts of deionized water and stir at 25–95°C until completely dissolved to obtain solution B;
[0019] Add solution B to solution A, stir the reaction at 25-95℃ for 1-3 hours, centrifuge, filter, and wash the filter cake with deionized water and ethanol to obtain Bi2S3 nanoparticles.
[0020] ② Preparation of Bi2S3@phenolic resin nanoparticles with egg yolk-eggshell structure: The Bi2S3 nanoparticles obtained in step ① and 0.7-0.9 parts of 3-aminophenol were added to 210-270 parts of deionized water and sonicated for 5-10 minutes. Then, 0.7-1 parts of ammonia water were added and stirred for 25-35 minutes. Then, 0.7-1 parts of formaldehyde aqueous solution were added and stirred for 25-35 minutes. Then, 50-200 parts of acetone were added to the solution and stirred for 10-60 minutes. The mixture was centrifuged, filtered, and the filter cake was washed with deionized water and ethanol. The mixture was dried at 55-75℃ for 6-20 hours to obtain Bi2S3@phenolic resin nanoparticles with egg yolk-eggshell structure.
[0021] ③ Dissolve 0.03–0.15 parts of FeSO4 in 10–12 parts of deionized water to obtain an aqueous solution of FeSO4;
[0022] Take 0.1 to 0.3 parts of the egg yolk-eggshell structure Bi2S3@phenolic resin nanoparticles obtained in step ② and add them to the reaction vessel. Evacuate to -0.1 MPa and maintain for 5 to 15 minutes. Add FeSO4 aqueous solution and stir to mix well. Return to atmospheric pressure, filter to remove excess liquid, dry the filter cake at 55 to 75°C for 6 to 20 hours, and sinter at high temperature under argon atmosphere to obtain egg yolk-eggshell structure Bi2S3@C / Fe3O4 nanoparticles.
[0023] Preferably, water bath heating is used during the stirring reaction in steps ① and ② to control the temperature of the reaction system. Preferably, the mass concentration of the ammonia water is 25-28%.
[0024] Preferably, the mass concentration of the formaldehyde aqueous solution is 35-37%.
[0025] Preferably, the high-temperature sintering temperature is 330–380°C, and the sintering time is 3–5 hours.
[0026] This invention also includes the application of egg yolk-eggshell structured Bi2S3@C / Fe3O4 nanoparticles, which are 3D printed into magnetic helmets using egg yolk-eggshell structured Bi2S3@C / Fe3O4 nanoparticles.
[0027] The present invention has the following advantages over the prior art:
[0028] The yolk-shell structured Bi2S3@C / Fe3O4 nanoparticles of this invention consist of a Bi2S3 core encapsulated within a carbon shell. Further doping with Fe3O4, these nanoparticles serve as multifunctional magnetic targeting nanoparticles, exhibiting high near-infrared absorption and strong photon attenuation characteristics, making them suitable for PTT-RT synergistic therapy in glioma treatment. In glioma treatment, the yolk-shell structured Bi2S3@C / Fe3O4 nanoparticles of this invention can reach the tumor site and achieve optimal therapeutic effects at effective concentrations, and can preferentially accumulate at intracranial tumor sites under the guidance of an external magnetic field. The nanoparticle material synthesis process of this invention is easy to implement and has high biosafety. The application of 3D-printed magnetic helmets can be extended to other parts of the human body, providing an industrially viable solution for the precision treatment of gliomas.
[0029] The present invention relates to Bi2S3@C / Fe3O4 nanoparticles with an egg yolk-shell structure, which for the first time integrates the photothermal / radiotherapy sensitization of Bi2S3, the magnetic targeting of Fe3O4, and the biocompatibility of the carbon shell into an egg yolk-shell structure, achieving a three-in-one treatment of "targeted delivery-photothermal ablation-radiotherapy sensitization". This material achieves a breakthrough in penetration depth, and solves the skull penetration limitation of photothermal therapy through magnetic targeting technology. At the same time, radiotherapy can be applied to deep tumors, synergistically covering the entire tumor area. The Bi2S3 core can achieve highly efficient near-infrared photothermal conversion and X-ray attenuation, with the near-infrared photothermal conversion efficiency reaching up to 37.4%. The phenolic resin carbon shell enhances the stability and biocompatibility of the Bi2S3 colloidal material, and Fe3O4 doping enables magnetic targeting. Attached Figure Description
[0030] Figure 1 The images show the SEM results of the Bi2S3 nanoparticles obtained in step ①, the egg yolk-eggshell structure Bi2S3@phenolic resin nanoparticles (Bi2S3@C) obtained in step ②, the dried filter cake obtained in step ③, and the egg yolk-eggshell structure Bi2S3@C / Fe3O4 nanoparticles obtained in Example 5.
[0031] Figure 2 The TEM results of Bi2S3 nanoparticles obtained in step ①, Bi2S3@phenolic resin nanoparticles with egg yolk-eggshell structure (Bi2S3@C) obtained in step ②, dried filter cake obtained in step ③, and Bi2S3@C / Fe3O4 nanoparticles with egg yolk-eggshell structure are shown in Example 5.
[0032] Figure 3 The images show the XRD results of the Bi2S3 nanoparticles obtained in step ①, the egg yolk-eggshell structure Bi2S3@phenolic resin nanoparticles (Bi2S3@C) obtained in step ②, the dried filter cake obtained in step ③, and the egg yolk-eggshell structure Bi2S3@C / Fe3O4 nanoparticles.
[0033] Figure 4 The image shows the FT-IR spectra of the Bi2S3 nanoparticles obtained in step ①, the egg yolk-eggshell structure Bi2S3@phenolic resin nanoparticles (Bi2S3@C) obtained in step ②, the dried filter cake obtained in step ③, and the egg yolk-eggshell structure Bi2S3@C / Fe3O4 nanoparticles obtained in Example 5.
[0034] Figure 5 Energy dispersive X-ray spectra of Bi2S3@C / Fe3O4 nanoparticles;
[0035] Figure 6 Elemental mapping image of Bi2S3@C / Fe3O4 nanoparticles;
[0036] Figure 7 The full spectrum of X-ray photoelectron energy of Bi2S3@C / Fe3O4 nanoparticles;
[0037] Figure 8 Fine X-ray photoelectron energy spectrum of Bi2S3@C / Fe3O4 nanoparticles;
[0038] Figure 9 The N adsorption / desorption isotherms of Bi2S3@C / Fe3O4 nanoparticles (inset: pore size distribution curve);
[0039] Figure 10 The zeta potential distribution of Bi2S3@C / Fe3O4 nanoparticles;
[0040] Figure 11 Magnetization curves of Bi2S3@C / Fe3O4 nanoparticles (Inset: Enlarged MH hysteresis loop)
[0041] Figure 12 The UV-Vis-NIR absorption spectrum of Bi2S3@C / Fe3O4 nanoparticles.
[0042] Figure 13 Bi2S3@C / Fe3O4 nanoparticles (0.5 mg / mL) -1 Different power densities (0.5–1.5 W / cm²) -2 The temperature rise curve under ( );
[0043] Figure 14 Bi2S3@C / Fe3O4 nanoparticles (0.5 mg / mL) -1 Photothermal diagrams at different power densities;
[0044] Figure 15 Bi2S3@C / Fe3O4 nanoparticles (0.5 mg / mL) -1 Photothermal conversion efficiency test graph (1W cm⁻¹) -2 )
[0045] Figure 16 Bi2S3@C / Fe3O4 nanoparticles (0.5 mg / mL) -1 ) Relationship between cooling time and -lnθ;
[0046] Figure 17 Bi2S3@C / Fe3O4 nanoparticles (0.5 mg / mL) -1 Cyclic stability plot (1W cm) -2 )
[0047] Figure 18The relative survival rates of U87MG-Luc and U251 cells after treatment with different concentrations of Bi2S3@C / Fe3O4 are plotted.
[0048] Figure 19 Schematic diagram of LDH release in U87MG-Luc cells under different treatments (n=3; Bi2S3@C / Fe3O4 0.5mg / mL);
[0049] Figure 20 Image showing the live / dead staining results of U87MG-Luc cells after different treatments. Scale bar: 200μm.
[0050] Figure 21 Qualitative characterization of DNA fragmentation under different treatments, scale bar: 50 μm;
[0051] Figure 22 The images show a magnetic helmet for a mouse, where a is a model image and b is a physical image.
[0052] Figure 23 Fluorescence images of U87MG-Luc tumor-bearing mice at different time points after intravenous injection of Cy5.5-labeled Bi2S3@C / Fe3O4 nanoparticles;
[0053] Figure 24 This is a quantitative analysis diagram of bioluminescence in tumor-bearing mice;
[0054] Figure 25 To determine the growth of intracranial glioblastoma by bioluminescence analysis of U87MG cells expressing luciferase on days 0, 7, and 14;
[0055] Among them, Control is the control group, NPs is the nanoparticle group, NIR is the near-infrared group, RT is the radiotherapy group, NPs+NIR is the nanoparticle + near-infrared group, NPs+RT is the nanoparticle + radiotherapy group, NPs+NIR+RT is the nanoparticle + near-infrared + radiotherapy group, and NPs+EMF is the nanoparticle + magnetic helmet group. Detailed Implementation
[0056] The purpose of this invention is to provide a yolk-shell structured Bi2S3@C / Fe3O4 nanoparticle, its preparation method, and its application. The invention will be further described below with reference to specific embodiments.
[0057] Example 1
[0058] A method for preparing Bi2S3@C / Fe3O4 nanoparticles with an egg yolk-eggshell structure includes the following steps:
[0059] ① Preparation of Bi2S3 nanoparticles: 0.3g bismuth ammonium citrate, 0.2g polyvinylpyrrolidone and 25g deionized water were added to a reaction vessel, heated to 25℃ and stirred to obtain solution A;
[0060] Add 0.75g of thioacetamide to 10g of deionized water and stir at 25℃ until completely dissolved to obtain solution B;
[0061] Solution B was added to solution A, and the mixture was stirred at 25°C for 3 hours. After centrifugation and filtration, the filter cake was washed with deionized water and ethanol to obtain Bi2S3 nanoparticles.
[0062] ② Preparation of Bi2S3@phenolic resin nanoparticles with egg yolk-eggshell structure: The Bi2S3 nanoparticles obtained in step ① and 0.7g of 3-aminophenol were added to 210g of deionized water and sonicated for 5 minutes. Then, 0.7g of ammonia was added and stirred for 25 minutes. Next, 0.7g of formaldehyde aqueous solution was added and stirred for 25 minutes. Finally, 50g of acetone was added to the solution and stirring was continued for 10 minutes. The mixture was centrifuged, filtered, and the filter cake was washed with deionized water and ethanol. The mixture was then dried at 55℃ for 6 hours to obtain the Bi2S3@phenolic resin nanoparticles with egg yolk-eggshell structure. The mass concentration of the ammonia was 25%, and the mass concentration of the formaldehyde aqueous solution was 35%.
[0063] ③ Dissolve 0.03g of FeSO4 in 10g of deionized water to obtain an aqueous solution of FeSO4;
[0064] Take 0.1g of the egg yolk-eggshell structure Bi2S3@phenolic resin nanoparticles obtained in step ② and add them to the reaction vessel. Evacuate to -0.1MPa and maintain for 5 minutes. Add FeSO4 aqueous solution, stir and mix well, restore to atmospheric pressure, filter to remove excess liquid, dry the filter cake at 55℃ for 6 hours, and sinter at 330℃ for 5 hours under argon atmosphere to obtain egg yolk-eggshell structure Bi2S3@C / Fe3O4 nanoparticles.
[0065] Example 2
[0066] A method for preparing Bi2S3@C / Fe3O4 nanoparticles with an egg yolk-eggshell structure includes the following steps:
[0067] ①Preparation of Bi2S3 nanoparticles: 1.3g of bismuth ammonium citrate, 1g of polyvinylpyrrolidone and 50g of deionized water were added to a reaction vessel, heated to 95℃ and stirred to obtain solution A;
[0068] Add 3g of thioacetamide to 50g of deionized water and stir at 95℃ until completely dissolved to obtain solution B;
[0069] Solution B was added to solution A, and the mixture was stirred at 95°C for 1 hour. After centrifugation and filtration, the filter cake was washed with deionized water and ethanol to obtain Bi2S3 nanoparticles.
[0070] ② Preparation of Bi2S3@phenolic resin nanoparticles with egg yolk-eggshell structure: The Bi2S3 nanoparticles obtained in step ① and 0.9g of 3-aminophenol were added to 270g of deionized water and sonicated for 10 minutes. 1g of ammonia was added and stirred for 35 minutes. 1g of formaldehyde aqueous solution was added and stirred for 35 minutes. 200g of acetone was added to the solution and stirring was continued for 60 minutes. The mixture was centrifuged, filtered, and the filter cake was washed with deionized water and ethanol. The mixture was dried at 75℃ for 20 hours to obtain Bi2S3@phenolic resin nanoparticles with egg yolk-eggshell structure. The mass concentration of the ammonia was 28%, and the mass concentration of the formaldehyde aqueous solution was 37%.
[0071] ③ Dissolve 0.15g of FeSO4 in 12g of deionized water to obtain an aqueous solution of FeSO4;
[0072] Take 0.3g of the egg yolk-eggshell structure Bi2S3@phenolic resin nanoparticles obtained in step ② and add them to the reaction vessel. Evacuate to -0.1MPa and maintain for 15 minutes. Add FeSO4 aqueous solution, stir and mix well, restore to atmospheric pressure, filter to remove excess liquid, dry the filter cake at 75℃ for 20 hours, and sinter at 380℃ for 3 hours under argon atmosphere to obtain egg yolk-eggshell structure Bi2S3@C / Fe3O4 nanoparticles.
[0073] Example 3
[0074] A method for preparing Bi2S3@C / Fe3O4 nanoparticles with an egg yolk-eggshell structure includes the following steps:
[0075] ① Preparation of Bi2S3 nanoparticles: 0.5g bismuth ammonium citrate, 0.5g polyvinylpyrrolidone and 40g deionized water were added to a reaction vessel, heated to 55℃ and stirred to obtain solution A;
[0076] Add 2g of thioacetamide to 30g of deionized water and stir at 55℃ until completely dissolved to obtain solution B;
[0077] Solution B was added to solution A, and the mixture was stirred at 55°C for 2 hours. After centrifugation and filtration, the filter cake was washed with deionized water and ethanol to obtain Bi2S3 nanoparticles.
[0078] ② Preparation of Bi2S3@phenolic resin nanoparticles with egg yolk-eggshell structure: The Bi2S3 nanoparticles obtained in step ① and 0.75g of 3-aminophenol were added to 230g of deionized water and sonicated for 6 minutes. 0.8g of ammonia was added and stirred for 28 minutes. 0.8g of formaldehyde aqueous solution was added and stirred for 28 minutes. 80g of acetone was added to the solution and stirring was continued for 40 minutes. The mixture was centrifuged, filtered, and the filter cake was washed with deionized water and ethanol. The mixture was dried at 60℃ for 8 hours to obtain Bi2S3@phenolic resin nanoparticles with egg yolk-eggshell structure. The mass concentration of the ammonia was 26%, and the mass concentration of the formaldehyde aqueous solution was 36%.
[0079] ③ Dissolve 0.08g of FeSO4 in 11g of deionized water to obtain an aqueous solution of FeSO4;
[0080] Take 0.15g of the egg yolk-eggshell structure Bi2S3@phenolic resin nanoparticles obtained in step ② and add them to the reaction vessel. Evacuate to -0.1MPa and maintain for 8 minutes. Add FeSO4 aqueous solution, stir and mix well, restore to atmospheric pressure, filter to remove excess liquid, dry the filter cake at 60℃ for 8 hours, and sinter at 340℃ for 3.5 hours under argon atmosphere to obtain egg yolk-eggshell structure Bi2S3@C / Fe3O4 nanoparticles.
[0081] Example 4
[0082] A method for preparing Bi2S3@C / Fe3O4 nanoparticles with an egg yolk-eggshell structure includes the following steps:
[0083] ①Preparation of Bi2S3 nanoparticles: 1.2g of bismuth ammonium citrate, 0.8g of polyvinylpyrrolidone and 40g of deionized water were added to a reaction vessel, heated to 70℃, and stirred to obtain solution A;
[0084] Add 2g of thioacetamide to 30g of deionized water and stir at 65℃ until completely dissolved to obtain solution B;
[0085] Solution B was added to solution A, and the mixture was stirred at 70°C for 2 hours. After centrifugation and filtration, the filter cake was washed with deionized water and ethanol to obtain Bi2S3 nanoparticles.
[0086] ② Preparation of Bi2S3@phenolic resin nanoparticles with egg yolk-eggshell structure: The Bi2S3 nanoparticles obtained in step ① and 0.75g of 3-aminophenol were added to 220g of deionized water and sonicated for 6 minutes. 0.9g of ammonia was added and the mixture was stirred for 28 minutes. 0.9g of formaldehyde aqueous solution was added and the mixture was stirred for 30 minutes. 150g of acetone was added to the solution and the mixture was stirred for another 50 minutes. The mixture was centrifuged, filtered, and the filter cake was washed with deionized water and ethanol. The mixture was dried at 60℃ for 12 hours to obtain Bi2S3@phenolic resin nanoparticles with egg yolk-eggshell structure. The mass concentration of the ammonia was 26%, and the mass concentration of the formaldehyde aqueous solution was 36%.
[0087] ③ Dissolve 0.1g of FeSO4 in 10g of deionized water to obtain an aqueous solution of FeSO4;
[0088] Take 0.25g of the egg yolk-eggshell structure Bi2S3@phenolic resin nanoparticles obtained in step ② and add them to the reaction vessel. Evacuate to -0.1MPa and maintain for 12 minutes. Add FeSO4 aqueous solution and stir to mix well. Return to atmospheric pressure, filter to remove excess liquid, dry the filter cake at 70℃ for 15 hours, and sinter at 350℃ for 4 hours under argon atmosphere to obtain egg yolk-eggshell structure Bi2S3@C / Fe3O4 nanoparticles.
[0089] Example 5
[0090] A method for preparing Bi2S3@C / Fe3O4 nanoparticles with an egg yolk-eggshell structure includes the following steps:
[0091] ① Preparation of Bi2S3 nanoparticles: 0.64g of bismuth ammonium citrate, 0.3g of polyvinylpyrrolidone and 30g of deionized water were added to a reaction vessel, heated to 90℃ and stirred to obtain solution A;
[0092] Add 1.12g of thioacetamide to 30g of deionized water and stir at 90℃ until completely dissolved to obtain solution B;
[0093] Solution B was added to solution A, and the mixture was stirred at 90°C for 2 hours. After centrifugation and filtration, the filter cake was washed with deionized water and ethanol to obtain Bi2S3 nanoparticles.
[0094] ② Preparation of Bi2S3@phenolic resin nanoparticles with egg yolk-eggshell structure: The Bi2S3 nanoparticles obtained in step ① and 0.8 g of 3-aminophenol were added to 240 g of deionized water and sonicated for 8 minutes. Then, 0.8 g of ammonia water was added and stirred for 30 minutes. Next, 0.8 g of formaldehyde aqueous solution was added and stirred for 30 minutes. Finally, 160 g of acetone was added to the solution and stirring was continued for 30 minutes. The mixture was centrifuged, filtered, and the filter cake was washed with deionized water and ethanol. The mixture was then dried at 60°C for 12 hours to obtain the Bi2S3@phenolic resin nanoparticles with egg yolk-eggshell structure. The mass concentration of the ammonia water was 27%, and the mass concentration of the formaldehyde aqueous solution was 36%.
[0095] ③ Dissolve 0.14g of FeSO4 in 11g of deionized water to obtain an aqueous solution of FeSO4;
[0096] Take 0.2g of the egg yolk-eggshell structure Bi2S3@phenolic resin nanoparticles obtained in step ② and add them to the reaction vessel. Evacuate to -0.1MPa and maintain for 10 minutes. Add FeSO4 aqueous solution and stir to mix well. Return to atmospheric pressure, filter to remove excess liquid, dry the filter cake at 60℃ for 12 hours, and sinter at 360℃ for 4 hours under argon atmosphere to obtain egg yolk-eggshell structure Bi2S3@C / Fe3O4 nanoparticles.
[0097] In Example 5, the Bi2S3 nanoparticles obtained in step ①, the yolk-shell structured Bi2S3@phenolic resin nanoparticles obtained in step ②, the dried filter cake obtained in step ③, and the yolk-shell structured Bi2S3@C / Fe3O4 nanoparticles were sequentially analyzed by scanning electron microscopy (SEM), transmission electron microscopy (TEM), XRD, and FT-IR spectroscopy. The morphology of the samples was analyzed using field emission scanning electron microscopy (SEM, JSM-7800F, JEOL). Low-resolution and high-resolution transmission electron microscopy (TEM) data were acquired using a JEOL JEM-2100 instrument (equipped with a field emission gun, operating voltage 200kV). Powder X-ray diffraction (XRD, DMAX-2500PC, Rigaku) was performed at 10° min. -1The crystal structure and phase composition were determined at a scanning speed of [missing information]. X-ray photoelectron spectroscopy (XPS) data were acquired using a Shimadzu AXIS SUPRA spectrometer. Fourier transform infrared (FT-IR) spectroscopy analysis was performed using an IS50 spectrometer with KBr pellet technique. The zeta potential was measured using a Malvern Nano ZSE instrument. Absorption spectra were collected using a UV-Vis spectrophotometer (UV-vis, SPECORD 200 PLUS, Analytick Jena). The magnetic properties of the material were studied using a vibrating sample magnetometer (VSM, Lakeshore 7404). The specific surface area and pore size distribution of the samples were studied using an APSP surface area and porosity analyzer (Micromeritics). The temperature of the samples and mice was recorded using a FLIR A310 thermal imager, with a near-infrared laser (808nm, LSR808N-3W-FC, Ningbo Yuanming Laser Technology Co., Ltd.) as the irradiation source. SEM results are shown below. Figure 1 As shown, the TEM detection results are as follows: Figure 2 As shown, the XRD detection results are as follows: Figure 3 As shown, the FT-IR spectral detection results are as follows: Figure 4 As shown.
[0098] Depend on Figure 1 and Figure 2 As can be seen, the Bi2S3@C / Fe3O4 nanoparticles of this invention are regularly spherical, possessing a typical yolk-shell structure, with a clear boundary between the Bi2S3 core layer and the C shell layer, and Fe3O4 uniformly distributed within the carbon shell layer; Figure 1 It can also be seen that this method successfully synthesized Bi2S3 nanoparticles with uniform particle size (approximately 54.37 nm) and regular morphology. Using these Bi2S3 nanoparticles as templates, Bi2S3@C particles were prepared by carbon coating via phenolic reaction, significantly increasing the particle size to 93.36 nm. This external carbon layer facilitated the subsequent introduction of an iron source. Fe3O4 was introduced through in-situ crystallization under negative pressure, further increasing the particle size to 98.92 nm. Subsequently, Bi2S3@C / Fe3O4 nanoparticles with an average diameter of approximately 80.91 nm and regular morphology were synthesized through in-situ decomposition and oxidation of FeSO4.
[0099] Figure 2 TEM images confirmed the microstructural transformation during the synthesis of Bi2S3@C / Fe3O4 particles, showing effective dispersion of the Bi2S3 precursor core. Carbon coating promoted the formation of the yolk-shell structure, creating additional space for the introduction of the iron source. Ultimately, Bi2S3@C / Fe3O4 nanoparticles with regular morphology, uniform size, and well-dispersed yolk-shell structure were successfully synthesized via in-situ reaction, enhancing their potential functionality.
[0100] Depend on Figure 3 It can be seen that the Bi2S3@C / Fe3O4 nanoparticles obtained in this invention contain characteristic peaks of Bi2S3 and Fe3O4, exhibit good crystallinity, revealing the crystal structure at each stage of synthesis and further elucidating the synthesis mechanism of Bi2S3@C / Fe3O4. Fourier transform infrared (FT-IR) spectra of the products were obtained at each stage of the Bi2S3@C / Fe3O4 nanoparticle synthesis, and the characteristic absorption peaks of different functional groups verified the chemical process and structural evolution of the material. Figure 4 The presence of surface hydroxyl groups, carbon-carbon double bonds, and iron-oxygen groups in the products obtained from each step can be detected, and the gradual changes in characteristic peaks during the synthesis steps perfectly match the design concept of "core-shell-functional doping". FT-IR data provide evidence for the photothermal conversion (Bi2S3 chemical structure), magnetic response (Fe3O4), and biocompatibility (carbon shell functional groups) of the material.
[0101] The basic physicochemical properties of the Bi2S3@C / Fe3O4 nanoparticles obtained in Example 5 were comprehensively characterized, among which... Figure 5 Energy-dispersive X-ray spectroscopy, Figure 6 For element mapping images, Figure 7 and Figure 8 X-ray photoelectron spectroscopy, Figure 9 The N adsorption / desorption isotherms are shown in the inset (pocket image: pore size distribution curve). Figure 10 For zeta potential distribution, Figure 11 The magnetization curve (inset: enlarged MH hysteresis loop) is shown. Figure 12 This is the ultraviolet-visible-near-infrared absorption spectrum. Scale bar: 50 nm.
[0102] Figure 5 The energy-dispersive X-ray (EDX) spectrum of Bi₂S₃@C / Fe₃O₄ nanoparticles is shown, where the characteristic peaks of Bi, S, Fe, C, and O are clearly distinguishable, indicating that the material composition is consistent with the expected structure. Although the Fe peak is not very prominent due to the low Fe concentration and instrument sensitivity limitations. Figure 6 The elemental mapping images further confirmed the uniform distribution of Bi, S, Fe, C, and O in the sample, providing preliminary evidence for the successful synthesis of the Bi2S3@C / Fe3O4 composite material. To further analyze the chemical composition and electronic structure, Figure 7 and 8 The X-ray photoelectron spectroscopy (XPS) data were presented, in which... Figure 7 To obtain the full spectrum, analyze the approximate presence of elements; Figure 8 To obtain a detailed spectrum, the valence states of elements were analyzed. The binding energy peaks of Bi 4f and S 2p were observed. Figure 8 -I) confirmed the presence of Bi2S3, while the C1s spectrum ( Figure 8 -II) shows binding energy signals for CC, CO, and OC=O groups, indicating the presence of carbon functional groups on the material surface. Fe 2p spectrum ( Figure 8 -III) shows Fe 3+ and Fe 2+ The characteristic peaks confirmed the formation of the Fe3O4 phase. (O 1s spectrum) Figure 8 -IV) further indicates the presence of CO, C=O and Fe-O functional groups, suggesting an interaction between iron oxide and the carbon moiety.
[0103] Figure 9 The nitrogen adsorption-desorption isotherm is a typical type IV curve, indicating mesoporous characteristics. The specific surface area, determined by the Brunauer-Emmett-Teller (BET) method, is 81.1073 m². 2 / g, the average pore size calculated using the Barrett-Joyner-Halenda (BJH) method is 39.5849 nm (see Figure 9 (Illustration). These findings demonstrate that the Bi2S3@C / Fe3O4 nanocomposites possess a large specific surface area and optimized pore structure, significantly improving their efficiency for drug delivery applications. Figure 10 The zeta potential distribution of Bi2S3@C / Fe3O4 nanoparticles is shown, with an average value of -24.43±0.06mV, indicating excellent dispersion stability in solution. Figure 11 The magnetization curves of the Bi2S3@C / Fe3O4 nanoparticle sample are shown, with a saturation magnetization (Ms) of 0.94 emu / g, indicating significant magnetic response characteristics. The inset is a magnified view of the MH hysteresis loop, confirming the superparamagnetism of the material, which is crucial for magnetic separation or targeted applications. Figure 12 The ultraviolet-visible-near-infrared absorption spectrum of Bi2S3@C / Fe3O4 nanoparticles shows broad absorption in the wavelength range of 300-900 nm, with an absorbance of 0.76 at 808 nm, making this material very suitable for photothermal applications.
[0104] Energy-dispersive X-ray (EDX) / X-ray photoelectron spectroscopy (XPS) confirmed the ternary structure of "Bi2S3 core-carbon shell-Fe3O4". Nitrogen adsorption and zeta potential measurements demonstrated the advantages of the mesoporous structure and dispersion. Magnetization hysteresis and UV-Vis-NIR spectroscopy analysis verified the magnetic response and photothermal potential, thus completing the logical chain from "structure (core-shell-doping) to performance (magnetic / photothermal properties / biocompatibility) to application (synergistic therapy)". This design endows Bi2S3@C / Fe3O4 with multiple composite functions: ① photothermal conversion (Bi2S3) + radiosensitization (high Z element Bi / Fe); ② magnetic targeting (Fe3O4) + biocompatibility (carbon shell functional groups); ③ drug loading (mesoporous carbon shell). This study provides a solid materials science foundation for in vitro and in vivo therapeutic experiments.
[0105] In vitro photothermal conversion test
[0106] Photothermal therapy relies on the absorption of near-infrared light; therefore, the photothermal performance of the photothermal converter is crucial to its efficacy. The photothermal properties of synthesized Bi2S3@C / Fe3O4 nanoparticles (NPs) were systematically analyzed in vitro. The photothermal effect of the nanoparticles was evaluated at different power densities at a concentration of 0.5 mg / mL. Figures 13-17 As shown.
[0107] Figure 13 To investigate the correlation between temperature rise and power density, under 808nm laser irradiation, the power density ranged from 0.5 to 1.5 W / cm². 2 After irradiation for 10 minutes, the temperature of the nanoparticles increased significantly with increasing power density, reaching a maximum of 55.21℃, and then gradually stabilized due to heat dissipation. Simultaneously, the temperature changes of the solution were recorded using an infrared thermal imager, providing a more intuitive representation through a two-dimensional color graph, such as... Figure 14 As shown.
[0108] By recording the complete heating and cooling cycle, such as Figure 15 and Figure 16 As shown, and using the photothermal conversion efficiency calculation formula and the absorbance of the nanoparticles at 808 nm, the photothermal conversion efficiency was calculated to be 37.41%. To evaluate the photothermal stability of the Bi2S3@C / Fe3O4 nanoparticles, five laser-switched cycle tests were conducted. The results show that the high-temperature performance did not change significantly after five cycles, indicating that it possesses excellent photothermal stability. Figure 17 As shown. In summary, the Bi2S3@C / Fe3O4 nanoparticles obtained in this invention not only possess excellent photothermal conversion efficiency and stability, but also have considerable potential for tumor cell ablation in photothermal therapy.
[0109] Cell uptake and in vitro cytotoxicity assay
[0110] The accumulation of nanoparticles in tumor cells is crucial for enhancing anti-tumor effects. After successfully synthesizing Bi2S3@C / Fe3O4 nanoparticles, their cellular uptake and in vitro cytotoxicity were systematically investigated.
[0111] Specifically, U87MG-Luc cells were cultured in 100×15mm cell culture dishes for 24 hours to ensure cell adhesion. Subsequently, the cells were inoculated with 0.5 mg / mL... -1 Cells were co-cultured with the concentrated nanoparticles for 6 h. After co-culture, cells were digested with trypsin, collected by centrifugation, and fixed with 2.5% glutaraldehyde. The precipitate was washed three times with 0.1 M phosphate buffer (pH 7.4) and pre-embedded. The sample was fixed with 1% osmium tetroxide at room temperature and dehydrated with graded ethanol. Finally, the sample was embedded in resin. Ultrathin sections (60-80 nm) were prepared using an ultramicrotome (Leica UC7, Germany) and mounted on a 150-mesh copper grid. The sections were double-stained with 2% uranium acetate ethanol saturated solution and 2.6% lead citrate. The prepared samples were observed and imaged using a transmission electron microscope (TEM; HT7800, Hitachi, Japan). The results showed that Bi2S3@C / Fe3O4 nanoparticles were significantly internalized by cells. This successful cellular uptake lays a solid foundation for subsequent in vitro and in vivo experiments to verify the therapeutic effects of nanoparticles. The in vitro cellular effects of Bi2S3@C / Fe3O4 are as follows: Figures 18-21 As shown.
[0112] To evaluate the cytotoxicity of Bi2S3@C / Fe3O4 nanoparticles, U87MG-Luc and U251 cells were seeded at a density of 5000 cells per well in 96-well plates. Duchenne Modified Eagle Medium (DMEM, Gibco, USA) supplemented with 10% fetal bovine serum and 1% penicillin-streptomycin solution was used as the culture medium. Culture conditions were set at 37°C and 5% CO2. Subsequently, different concentrations of nanoparticles were added, and cells were incubated for 24 h. The final concentrations of nanoparticles in the medium were 0, 0.1, 0.3, 0.5, 0.7, and 0.9 mg / mL. -1 The control group received an equal volume of phosphate-buffered saline (PBS). Cell viability was assessed using a cell counting kit-8 (CCK-8). Figure 18 As shown, the cytotoxicity of nanoparticles increases with increasing concentration. Notably, even at the highest concentration of 0.9 mg / mL, the cytotoxicity of nanoparticles does not increase. -1 At the same time, cytotoxicity was not significant, indicating that Bi2S3@C / Fe3O4 nanoparticles have excellent biocompatibility and meet the basic requirements for further biomedical applications.
[0113] Use 0.5 mg mL -1The concentration of nanoparticles was determined, and the effects of photothermal therapy and radiotherapy were further investigated using lactate dehydrogenase (LDH) release assays. Compared with the control group, the cell viability of the Bi2S3@C / Fe3O4 nanoparticle group was significantly reduced (from 96.5% to 35.7% and from 97.6% to 26.7%, respectively) under near-infrared treatment alone and combined radiotherapy and near-infrared treatment. Figure 19 As shown. The effect of nanoparticles on eight groups of U87MG-Luc cells was evaluated using a live / dead cell kit, where live cells were stained green and dead cells were stained red, as shown. Figure 20 As shown, cell imaging data revealed strong PI signals associated with chromatin condensation in all cell nuclei of both the nanoparticle + near-infrared (NIIR) and nanoparticle + NIIR + radiotherapy (RT) groups. Notably, the signal was more pronounced in the NIIR + RT group, indicating more extensive cell death compared to the other groups, consistent with previously reported lactate dehydrogenase data. These findings not only demonstrate the excellent photothermal therapeutic effects of Bi2S3@C / Fe3O4 nanoparticles but also highlight the synergistic effect between photothermal therapy (PTT) and radiotherapy (RT), reinforcing the significant potential of combining these two technologies in medicine.
[0114] The enhanced radioactivity was attributed to DNA breakage. DNA damage was characterized using phosphorylated histone H2AX (γ-H2AX). The control group did not show a significant γ-H2AX fluorescence signal, as... Figure 21 As shown, limited γ-H2AX foci were detected only in the radiotherapy group and the near-infrared + radiotherapy group. In contrast, significantly more γ-H2AX foci were observed in the nanoparticle + near-infrared and nanoparticle + radiotherapy groups, with the highest number observed in the nanoparticle + near-infrared + radiotherapy group, indicating that the enhanced X-ray generation in the synergistic treatment induced substantial DNA damage. The enhanced signal in the nanoparticle + radiotherapy group indicates that the cells suffered significant DNA damage, although lactate dehydrogenase and live / dead staining assays did not show immediate cell death. The strong signal in the nanoparticle + near-infrared group is attributed to the superior photothermal effect of this treatment, leading to increased cell death. These results suggest that nanoparticle-mediated synergistic treatment is an effective method for killing U87MG-Luc cells. These findings consistently demonstrate the potential to induce DNA damage in U87MG-Luc cells by utilizing the combined sensitivity of photothermal therapy and radiotherapy.
[0115] In vivo targeted and synergistic therapy testing
[0116] Further evaluation was conducted on the in vivo distribution and tumor retention of the Bi2S3@C / Fe3O4 nanoparticles obtained in this invention. The fluorescent dye Cy5.5 was successfully loaded onto the Bi2S3@C / Fe3O4 nanoparticles. Fluorescent imaging was achieved and stability was ensured by utilizing the hydrophobic interactions and van der Waals forces between the dye and the nanoparticles. To achieve precise localization, a customized magnetic helmet was fabricated for nude mice using 3D printing technology, such as... Figure 22 As shown. Subsequently, the in vivo biodistribution and pharmacokinetics of Cy5.5-labeled Bi2S3@C / Fe3O4 nanoparticles were evaluated after intravenous administration. Figure 23 As shown, the fluorescence intensity at the tumor site in nude mice wearing the magnetic helmet was significantly stronger than that in mice not wearing the helmet, highlighting the enhanced tumor aggregation ability of Bi2S3@C / Fe3O4 nanoparticles. Based on these in vivo imaging and pharmacokinetic findings, we propose that the optimal time point for irradiation therapy is 12 hours post-injection. The magnetic helmet addresses a key challenge in brain tumor treatment: inefficient drug delivery across the blood-brain barrier (BBB) and the resulting insufficient tumor accumulation. This system utilizes the superparamagnetism of Fe3O4 to translate external physical stimuli (magnetic field) into spatial control over the biodistribution of nanoparticles. This active targeting not only enhances tumor-specific accumulation but also reduces off-target toxicity, which is crucial for central nervous system (CNS) applications, as the protection of normal tissue is essential. The optimal 12-hour window is consistent with the pharmacokinetic characteristics of the mesoporous nanocarrier, ensuring sufficient time for the nanoparticles to extravasate across the blood-brain barrier (damaged in gliomas) and subsequently penetrate the tumor.
[0117] Encouraged by the in vitro experimental results demonstrating the cytotoxicity of Bi2S3@C / Fe3O4 nanoparticles against tumor cells, we further investigated the in vivo therapeutic effects of the nanoparticles. The in vivo therapeutic effects of the nanoparticles were evaluated using an orthotopic mouse model of glioma. U87MG-Luc tumor-bearing mice were randomly divided into 8 groups (n=3 per group) and received different treatment regimens. Figure 24 and Figure 25The changes in fluorescence intensity within tumors of tumor-bearing mice were observed. Results showed a significant increase in tumor fluorescence intensity in the control group, while tumor growth was effectively inhibited in both the nanoparticle + radiotherapy group (NPs + RT) and the nanoparticle + near-infrared group (NPs + NIR). Notably, the inhibitory effect of the nanoparticle + near-infrared group was less significant than that of the nanoparticle + radiotherapy group, but the former still showed slow tumor growth, consistent with in vitro cell experiments. These results indicate that nanoparticles enhance the efficacy of in vivo radiotherapy and photothermal therapy. The nanoparticle + near-infrared + radiotherapy group (NPs + NIR + RT) showed the most significant tumor inhibition. Compared with photothermal therapy and radiotherapy alone, synergistic treatment with nanoparticles significantly improved the therapeutic effect in tumor-bearing mice. Furthermore, H&E staining of major organs in each group showed low biotoxicity of the nanoparticles, with no obvious organ toxicity or side effects observed, collectively indicating that Bi2S3@C / Fe3O4 nanoparticles possess high biocompatibility and safety.
[0118] The egg yolk-eggshell structured Bi2S3@C / Fe3O4 nanoparticles prepared in Examples 1-5 of this invention include a carbon shell layer and a core layer, which are connected by a hollow layer. The carbon shell layer is made of phenolic resin carbon, and superparamagnetic Fe3O4 nanoparticles are uniformly distributed in the carbon shell layer. The core layer is made of Bi2S3 nanoparticles. The size of the egg yolk-eggshell structured Bi2S3@C / Fe3O4 nanoparticles is 75-110 nm, the diameter of the core layer is 40-60 nm, and the thickness of the carbon shell layer is 5-25 nm.
[0119] The saturation magnetization of the superparamagnetic Fe3O4 nanoparticles is 0.8–1.2 emu / g.
[0120] The drug, such as temozolomide, is loaded onto the yolk-shell structured Bi2S3@C / Fe3O4 nanoparticles.
Claims
1. A yolk-shell structured Bi2S3@C / Fe3O4 nanoparticle, characterized in that: It includes a carbon shell layer and a core layer, which are connected by a hollow layer. The carbon shell layer is made of phenolic resin carbon, and superparamagnetic Fe3O4 nanoparticles are uniformly distributed in the carbon shell layer. The core layer is made of Bi2S3 nanoparticles. The size of the Bi2S3@C / Fe3O4 nanoparticles in the yolk-shell structure is 75-110 nm. The diameter of the core layer is 40-60 nm, and the thickness of the carbon shell layer is 5-25 nm.
2. The egg yolk-shell structured Bi2S3@C / Fe3O4 nanoparticles according to claim 1, characterized in that: The saturation magnetization of the superparamagnetic Fe3O4 nanoparticles is 0.8–1.2 emu / g.
3. The egg yolk-shell structured Bi2S3@C / Fe3O4 nanoparticles according to claim 1, characterized in that: The drug is loaded onto the yolk-shell structured Bi2S3@C / Fe3O4 nanoparticles.
4. The method for preparing the yolk-shell structured Bi2S3@C / Fe3O4 nanoparticles according to claim 1, characterized in that: Includes the following steps: ①Preparation of Bi2S3 nanoparticles: Bismuth ammonium citrate, polyvinylpyrrolidone and deionized water were added to a reaction vessel, heated and stirred to obtain solution A; Thioacetamide was added to deionized water and stirred under heating until completely dissolved to obtain solution B; Solution B was added to solution A, the mixture was stirred, centrifuged, filtered, and the filter cake was washed with deionized water and ethanol to obtain Bi2S3 nanoparticles. ② Preparation of egg yolk-eggshell structured Bi2S3@phenolic resin nanoparticles: The Bi2S3 nanoparticles obtained in step ① and 3-aminophenol were added to deionized water, sonicated, ammonia water was added, stirred, formaldehyde aqueous solution was added, stirred and mixed, acetone was added to the solution, stirring was continued, centrifuged, filtered, the filter cake was washed with deionized water and ethanol, and dried to obtain egg yolk-eggshell structured Bi2S3@phenolic resin nanoparticles; ③ The egg yolk-eggshell structure Bi2S3@phenolic resin nanoparticles obtained in step ② are added to the reaction vessel, FeSO4 aqueous solution is added under vacuum, stirred and mixed, restored to atmospheric pressure, filtered to remove excess liquid, the filter cake is dried, and sintered at high temperature under argon atmosphere to obtain egg yolk-eggshell structure Bi2S3@C / Fe3O4 nanoparticles.
5. The method for preparing Bi2S3@C / Fe3O4 nanoparticles with an egg yolk-eggshell structure according to claim 5, characterized in that: Includes the following steps: ①Preparation of Bi2S3 nanoparticles: 0.3-1.3 parts by weight of bismuth ammonium citrate, 0.2-1 parts by weight of polyvinylpyrrolidone and 25-50 parts by weight of deionized water were added to a reaction vessel, heated to 25-95℃, and stirred to obtain solution A. Add 0.75–3 parts of thioacetamide to 10–50 parts of deionized water and stir at 25–95°C until completely dissolved to obtain solution B; Add solution B to solution A, stir the reaction at 25-95℃ for 1-3 hours, centrifuge, filter, and wash the filter cake with deionized water and ethanol to obtain Bi2S3 nanoparticles. ② Preparation of Bi2S3@phenolic resin nanoparticles with egg yolk-eggshell structure: The Bi2S3 nanoparticles obtained in step ① and 0.7-0.9 parts of 3-aminophenol were added to 210-270 parts of deionized water and sonicated for 5-10 minutes. Then, 0.7-1 parts of ammonia water were added and stirred for 25-35 minutes. Then, 0.7-1 parts of formaldehyde aqueous solution were added and stirred for 25-35 minutes. Then, 50-200 parts of acetone were added to the solution and stirred for 10-60 minutes. The mixture was centrifuged, filtered, and the filter cake was washed with deionized water and ethanol. The mixture was dried at 55-75℃ for 6-20 hours to obtain Bi2S3@phenolic resin nanoparticles with egg yolk-eggshell structure. ③ Dissolve 0.03 to 0.15 parts of FeSO4 in 10 to 12 parts of deionized water to obtain an aqueous solution of FeSO4; Take 0.1 to 0.3 parts of the egg yolk-eggshell structure Bi2S3@phenolic resin nanoparticles obtained in step ② and add them to the reaction vessel. Evacuate to -0.1 MPa and maintain for 5 to 15 minutes. Add FeSO4 aqueous solution and stir to mix well. Return to atmospheric pressure, filter to remove excess liquid, dry the filter cake at 55 to 75°C for 6 to 20 hours, and sinter at high temperature under argon atmosphere to obtain egg yolk-eggshell structure Bi2S3@C / Fe3O4 nanoparticles.
6. The method for preparing Bi2S3@C / Fe3O4 nanoparticles with an egg yolk-shell structure according to claim 6, characterized in that: The mass concentration of the ammonia water is 25-28%.
7. The method for preparing Bi2S3@C / Fe3O4 nanoparticles with an egg yolk-shell structure according to claim 6, characterized in that: The formaldehyde aqueous solution has a mass concentration of 35-37%.
8. The method for preparing Bi2S3@C / Fe3O4 nanoparticles with an egg yolk-shell structure according to claim 6, characterized in that: The high-temperature sintering temperature is 330–380℃, and the sintering time is 3–5 hours.
9. The application of the yolk-shell structured Bi2S3@C / Fe3O4 nanoparticles according to claim 1, characterized in that: Bi2S3@C / Fe3O4 nanoparticles with an egg yolk-eggshell structure were 3D printed into a magnetic helmet.